Preparation and characterization of silver nanoparticle loaded amorphous hydrogel of carboxymethylcellulose for infected wounds. (5th October 2015) - Das, Anup; Kumar, Ajay; Patil, Niranjan B.; Viswanathan, Chandra; Ghosh, Deepa
Highlights: Silver nanoparticle (SNP) loaded amorphous gel was developed for infected deep wounds. SNPs were developed in situ without using any toxic reducing agent or organic solvent. SNP–CMC exhibited high antibacterial activity against different strains including MRSA. Abstract: There is a growing demand for an appropriate and safe antimicrobial dressing to treat infected deep wounds. An amorphous gel formulation (SNP–CMC), containing silver nanoparticles (SNPs) and carboxymethylcellulose (CMC), was prepared in one step by the reduction of silver nitrate in situ . Spectrophotometric and microscopic analysis revealed that the SNPs were 7–21 nm in diameter. In simulated wound experiments, SNP–CMC gel was found to absorb 80.48 ± 4.69% w/w of saline and donate 17.43 ± 0.76% w/w of moisture within 24 h indicating its dual fluid affinity. Cytocompatibility of the gel was assessed by proliferation studies with primary human skin cells. The antimicrobial activity studies showed that SNP–CMC containing 50 ppm of SNPs was effective against the growth of both Gram negative and Gram positive strains including methicillin-resistant Staphylococcus aureus (MRSA). These results indicate that SNP–CMC could be ideal for the treatment of deep infected wounds.